Antibiotic Consumption Patterns in European Countries Might Be Associated with the Prevalence of Type 1 and 2 Diabetes - Ternák, Gábor; Németh, Márton; Rozanovic, Martin; Bogár, Lajos (Frontiers in Endocrinology, 2022)
Several publications have raised the issue that the development of diabetes precedes the alteration of the microbiome (dysbiosis) and the role of environmental factors. Antibiotic use induces dysbiosis, and we wanted to estimate the associations between the consumption of antibiotics and the prevalence of diabetes (both types 1 and 2; T1D and T2D, respectively) in European countries. If such an association exists, the dominant use antibiotic classes might be reflected in the prevalence rates of T1D and T2D in different countries. Comparisons were performed between the prevalence of diabetes estimated for 2019 and featured in the Diabetes Atlas and the average yearly consumption of antibiotic classes between 2010 and 2109, calculated from the European Centre for Disease Prevention and Control (ECDC) yearly reports on antibiotic consumption in Europe. Pearson’s correlation and variance analyses were used to estimate the possible relationship. Strong positive (enhancer) associations were found between the prevalence of T1D and the consumption of tetracycline (J01A: p = 0.001) and the narrow-spectrum penicillin (J01CE: p = 0.006; CF: p = 0.018). A strong negative (inhibitor) association was observed with broad-spectrum, beta-lactamase-resistant penicillin (J01CR: p = 0.003), macrolide (J01F: p = 0.008), and quinolone (J01M: p = 0.001). T2D showed significant positive associations with cephalosporin (J01D: p = 0.048) and quinolone (J01M: p = 0.025), and a non-significant negative association was detected with broad-spectrum, beta-lactamase-sensitive penicillin (J01CA: p = 0.067). Countries showing the highest prevalence rates of diabetes (top 10) showed concordance with the higher consumption of “enhancer” and the lower consumption of “inhibitor” antibiotics (top 10), as indicated by variance analysis. Countries with high prevalence rates of T1D showed high consumption of tetracycline (p = 0.015) and narrow-spectrum, beta-lactamase sensitive penicillin (p = 0.008) and low consumption of “inhibitor” antibiotics [broad-spectrum, beta-lactamase-resistant, combination penicillin (p = 0.005); cephalosporin (p = 0.036); and quinolone (p = 0.003)]. Countries with high prevalence rates of T2D consumed more cephalosporin (p = 0.084) and quinolone (p = 0.054) and less broad-spectrum, beta-lactamase-sensitive penicillin (p = 0.012) than did other countries. The development of diabetes-related dysbiosis might be related to the higher consumption of specific classes of antibiotics, showing positive (enhancer) associations with the prevalence of diabetes, and the low consumption of other classes of antibiotics, those showing negative (inhibitory) associations. These groups of antibiotics are different in T1D and T2D.